2018
DOI: 10.1371/journal.pone.0204283
|View full text |Cite
|
Sign up to set email alerts
|

Role of altered proteostasis network in chronic hypobaric hypoxia induced skeletal muscle atrophy

Abstract: BackgroundHigh altitude associated hypobaric hypoxia is one of the cellular and environmental perturbation that alters proteostasis network and push the healthy cell towards loss of muscle mass. The present study has elucidated the robust proteostasis network and signaling mechanism for skeletal muscle atrophy under chronic hypobaric hypoxia (CHH).MethodsMale Sprague Dawley rats were exposed to simulated hypoxia equivalent to a pressure of 282 torr for different durations (1, 3, 7 and 14 days). After CHH expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Our previous studies reported that HH-induced skeletal muscle protein loss is multifaced signaling pathways which include proteome imbalance, free radical medicated oxidative stress and inflammation, oxidative protein modification, enhanced degradative pathway, altered anabolic signaling and apoptosis. 2,8,11 The present study for the first time, evaluated the protective effect of UA against HH-induced skeletal muscle damage and protein loss. The antioxidant, antiinflammatory activity and increased protein content via upregulation of AkT pathway by administration of UA may have beneficial effect for maintaining muscle mass under hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies reported that HH-induced skeletal muscle protein loss is multifaced signaling pathways which include proteome imbalance, free radical medicated oxidative stress and inflammation, oxidative protein modification, enhanced degradative pathway, altered anabolic signaling and apoptosis. 2,8,11 The present study for the first time, evaluated the protective effect of UA against HH-induced skeletal muscle damage and protein loss. The antioxidant, antiinflammatory activity and increased protein content via upregulation of AkT pathway by administration of UA may have beneficial effect for maintaining muscle mass under hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies reported that HH‐induced skeletal muscle protein loss is multifaced signaling pathways which include proteome imbalance, free radical medicated oxidative stress and inflammation, oxidative protein modification, enhanced degradative pathway, altered anabolic signaling and apoptosis 2,8,11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding effects of hypoxia on GSK-3β activity in muscle, literature is scarce and inconclusive. Chronic hypobaric hypoxia increased the total abundance of GSK-3β in rat skeletal muscle but GSK-3β activity or phosphorylation status was not assessed [168]. In addition, hypoxia exposure reduced the phosphorylation of GSK-3β in C2C12 myoblasts suggesting enhanced GSK-3β activity [169].…”
Section: Hypoxiamentioning
confidence: 97%